REPRESENTATION OF NYI RORO KIDUL IN MYTH, LEGEND, AND POPULAR CULTURE - Ambar Andayani; Jupriono Jupriono (Anaphora : Journal of Language, Literary, and Cultural Studies, 2019)
Nyi Roro Kidul, Nyai Loro Kidul, or Nyai Ratu Kidul is a character of folk legend which has existedÂ  all along south coast of Java land: from East Java, to Middle Java and Jogjakarta, then to West Java and Banten. People along the south coast of Java island believe to myth of this legendary character as a beautiful and supernatural woman who has authority of devil realm in Indonesian Ocean (Indian Ocen) or Segoro Kidul (South Sea). The popularity of Nyi Roro Kidul has also become motivation for national film-making and TV media to produce many films and drama about this character. Although there are many similarities about the revelation, among regions, legend and mass culture (film, TV); the representations of Nyi Roro Kidul show differences in theme emphasis.Â  In East Javanese people, Nyi Roro Kidul is emphasized on the intention of people seeking wealth pesugihan (with the helping from devils) by sacrificing human soul for antidote. In Middle Javanese people, Kanjeng Ratu Kidul is representated as the take turn-wife of Sultans from Mataram, Sultan Panembahan Senopati to Sultans of Jogjakarta in the present time. The west Javanese people represents this figure as the princess of Pakuan Pajajaran Kingdom who is betrayed and abused, and throw away herself to jump into South Sea, then she incarnates as a beautiful and undefeated supernatural queen. On film and television, Nyi Roro Kidul is presented as a beautiful, sexy, cruel and sexual adventurer woman.